Hematological study of iron deficiency anemia and β thalassemia trait in Sindhi community of Bundelkhand region of Madhya Pradesh with predictive value of red cell indices to discriminate them - Dr. Amar Gangwani; Dr. Mitesh Shah (Tropical Journal of Pathology and Microbiology, 2019)
Background: Ethnic groups like Sindhis, Kutchis, Lohanas, Punjabis, few Muslim groups as well as few tribal populations have higher prevalence of hemoglobinopathy esespecially β thalassemia carriers. β Thalassemia traits are commonly misdiagnosed as iron deficiency anemia. Red cell indices are helpful to discriminate anemia and to detect subjects who have high probability of requiring appropriate follow up and to reduce unnecessary investigation cost. Aims and objectives: 1) To study red blood cell indices in all cases of microcytic hypochromic anemia. 2) Estimation of HbA2 levels and serum ferritin levels to confirmiron deficiency anemia and β thalassemia trait. 3) To evaluate the diagnostic values of various red cell indices in discriminating iron deficiency anemia and β thalassemia trait. Materials and methods: It is a prospective observation study carried out on Sindhi individuals of Sagar District of Bundelkhand region of Madhya Pradesh. Hemoglobin, RBC count, MCV, MCH and RDW were determined. Serum ferritin levels and HbA2 levels were detected. Result: Out of total 200 cases of Sindhi individuals 25 patients (12.5%) were grouped in β thalassemia trait while 175 patients (87.5%) were grouped in iron deficiency anemia group on the basis of HbA2 and serum ferritin level. Significant difference was found inmean MCV, MCH, RDW and RBC count and showed high sensitivity and specificity to discriminate iron deficiency anemia from β thalassemia. Conclusion: Sindhi community of Sagar district of Madhya Pradesh showed high prevalence of β thalassemia trait. Mass awareness and proper pre marriage genetic counseling and prenatal diagnosis should be done to reduce the burden of disease.